Removal of Matrix Interferences by Nano-MgO and Co-Adsorbents for Accurate Multi-Pesticide Residue Analysis in the Chinese Medicinal Herb, Paeoniae Radix Alba - Chunyu Wang; Xinquan Wang; Jiao Wang; Shanshan Di; Zhiwei Wang; Hao Xu; Huiyu Zhao; Changshan Zhao; Peipei Qi (Journal of Analytical Methods in Chemistry)
A simple, accurate, and high-throughput analytical method was developed to detect 123 pesticide residues in Chinese medicinal herb Paeoniae Radix Alba (PRA) by introducing nano-MgO as a highly efficient purification material based on quick, easy, cheap, effective, rugged, and safe (QuEChERS) design concept. Various PRA samples were extracted using 8 mL 0.5% acetic acid-acetonitrile solution and purified by a dispersive solid-phase extraction method with 30 mg nano-MgO, 40 mg primary secondary amine (PSA), and 40 mg octadecylsilane (C18) as the cleanup adsorbents, followed by liquid chromatography-tandem mass spectrometry (LC-MS/MS). 70.7% of pesticides showed a weak matrix effect after the purification process, indicating that this method can give the precise quantitative analysis of trace pesticides residue. The method was systematically validated under optimal conditions in five different kinds of PRA samples; good linearity was observed in the concentration range of 0.5–250 μg/L or 1–250 μg/L. Pesticide recovery in each sample spiked at concentrations of 20, 50, and 200 μg/kg ranged from 98.0% to 111% and the mean relative standard deviation ranged from 2.72% to 5.70%. Furthermore, the method comparison with the traditional QuEChERS method suggested the feasibility, advantages, and potential application prospect of the present method for the multi-pesticide residue analysis in various PRA samples.